Generic structures and linguistic resources in research article introductions in ethnic studies and industrial relations - Xianqing Luo (2019)
Academic scholars and postgraduate students across the world are generally expected to write and publish research articles in order to achieve professional advancement. Among the different sections of a research article, the Introduction section is known to be difficult, and practically all researchers acknowledge that it is more difficult to get started on a piece of research writing compared to other parts of a research article (Swales, 2004). This explains why there has been increasing interest in research relating to how the introductory section of a research article is written in different disciplines. Despite the voluminous literature, research article introductions (RAis) in certain social sciences have received little attention in previous genre-based studies, and this is particularly evident from a cross-disciplinary perspective. Such gaps in past investigations into research article introductions are especially noticeable in some fields such as Ethnic Studies (ES) and Industrial Relations (IR). In response to such lacunas, this study aims to (i) ascertain the rhetorical structures and salient linguistic resources in research article introductions on ES and IR, and (ii) identify the possible cross-disciplinary similarities and differences in the two fields of study. With respect to research methods, a total of 60 research articles were collected from six established journals in the two disciplines, each of which was represented by 30 articles obtained from three international refereed journals indexed in Web of Science. The investigation was conducted using (i) Swales' (1990, 2004) framework for analysing rhetorical moves, (ii) Urn's (2006, 2010, 2012, 2014, 2017) techniques for describing salient linguistic resources for rhetorical steps, and (iii) statements elicited from six specialist informants in the disciplines concerned. In regard to research results, I have found that 10 of the 11 rhetorical steps in Swales' 2004 model can be found in both disciplines. In terms of frequencies, 'establishing a territory' (in Move 1) constitutes an obligatory move in both disciplines, distinct differences in the frequencies of specific rhetorical categories have been found across ES and IR. So far as niche establishments are concerned, 'revealing a limitation in previous research' in Move 2 is found in a vast majority of the IR RAis, but only in a third of the ES RAis. When it comes to 'presenting the present work' in Move 3, 'summarising methods', 'stating the value of the present research' and 'outlining the structure of the paper' are incorporated in the majority of the IR RAis but only less than half of the ES RAis. Despite the existence of similar rhetorical steps in both disciplines, the categories of information provided in specific rhetorical steps differ markedly across ES and IR. My specialist informants have attributed the difference in frequencies of the steps to the use of differing philosophical assumptions and research paradigms in the disciplines concerned. In terms of linguistic resources, I have found that specific categories of pronouns, adjectives, verb forms, noun phrases, adverbials and interrogative structures are recurrently used in both disciplines; nevertheless, it has also been found that some cross-disciplinary differences exist in the use of specific categories of verb phrases and noun phrases in 'establishing a territory', 'indicating a gap', 'presenting RQs or hypotheses' and 'outlining the structure of the paper'. Based on the findings, a broad array of recurrent linguistic resources can be flexibly used to help materials developers and EAP instructors make informed choices while advising learners about the connections between writers' rhetorical strategies and their associated linguistic realisations in ES and IR. This study has also revealed how a relevant theoretical model for writing research introductions needs to be adjusted to take into consideration the actual practices of expert writers across different social science disciplines